The co-creation of antagonism : a lexical analysis of legal mobilizations over abortion in Colombia (2021)
Pro-life and pro-choice movements seemingly pursue drastically different objectives in the debate over abortion. Using the case of the legal mobilization before the Colombian Constitutional Court, I ask what happens when these two movements meet in the same institutional arena. To answer this question, I use an original dataset of legal files and apply to it distant reading techniques. Content and temporal analysis of judicial arguments over abortion reveals several counter-intuitive results. Contrary to a common assumption in the literature on antagonistic social movements, I show that the interaction between the two movements was not simply reactive. Instead, it led to the accidental co-creation of a common set of concepts, which gradually allowed each movement to position itself more clearly with respect to its rival.